Perspectives for NATO-Russia relations: forms of confrontation dominate - but dialogue not excluded - Klein, Margarete; Major, Claudia (2015)
Abstract: Institutional relations between NATO and Russia have been suspended since the illegal annexation of Crimea in 2014 and the war in eastern Ukraine. Conflicting ideas about Euro-Atlantic security have left the relationship deeply and lastingly damaged. This makes it all the more important to gain clarity about the determining factors and perspectives of the relationship. Its evolution over the coming five to ten years will also be shaped by future events, such as the NATO summit in Warsaw in 2016 and elections in the United States in 2016 and Russia in 2016 and 2018. External developments will play a significant role, too. (author's abstract)